2020
DOI: 10.7130/jject.47.8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin as an early indicator of acute kidney injury following pediatric cardiac surgery

Abstract: Risk factors for postoperative acute kidney injury (AKI) in patients undergoing cardiac surgery include ischemic-reperfusion injury associated with microcirculatory dysfunction due to non-physiological hemodynamics from cardiopulmonary bypass (CPB) and inflammatory reaction due to the exposure of blood to the CPB circuit 1). The incidence of AKI after CPB is reported to be as high as 20-30% 2). AKI severity has a linear relationship with mortality 3) , but it has been shown that even a 0.3mg/dL increase in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…These suggest that the values’ predictive performance is not consistent [ 14 ]. Similar results were observed in our study [ 12 ].…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…These suggest that the values’ predictive performance is not consistent [ 14 ]. Similar results were observed in our study [ 12 ].…”
Section: Introductionsupporting
confidence: 93%
“…Previous studies reported that urinary NGAL is more sensitive than other biomarkers for detecting AKI [ 13 , 14 , 21 ]. Compared to our previous study involving 64 patients, perioperative urinary NGAL showed more sensitivity in predicting AKI in this study since the number of patients is higher [ 12 ]. Significant differences in urinary NGAL during ICU admissions suggest that factors that caused the elevated NGAL levels were present during the intraoperative period.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…RACHS-1 category was found to be a risk factor associated with AKI after congenital cardiac surgeries. This is supported by Simon et al [14], Cardoso et al [15], and Wakamatsu et al [16] while, Lee et al [13] found that RACHS did not influence AKI incidence which may be attributed to their selection of RACHS-1 score ≥3 as a risk factor for AKI while 67 patients in that study had a lower score.…”
Section: Discussionsupporting
confidence: 52%
“…Previous reports have suggested that biomarkers such as NGAL and L-FABP are useful for the early detection of AKI by capturing peak values through multiple measurements. [6][7][8]11,12 However, in the present study, the timing of risk assessment was based on the assessment of spot urine samples at the time of ICU admission, which may have resulted in the peak values of NGAL and L-FABP not being captured.…”
Section: Discussionmentioning
confidence: 98%